Czasopiśmiennictwo regionalistyczne w Polsce – pojęcie, ideowe podstawy, cechy, zadania, typy - Kowalczyk, Ryszard (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2014)
Artykuł jest próbą usytuowania poznawczego terminu „czasopismo regionalistyczne”. Autor przedstawia to zagadnienie w czterech punktach. Najpierw wyjaśnia zakres znaczeniowy pojęcia „czasopismo regionalistyczne”. Następnie omawia podstawy ideowe czasopiśmiennictwa regionalistycznego, zaliczając do nich regionalizm i region, a także cechy, zadania i funkcje periodyków regionalistycznych. Na zakończenie przedstawia typy czasopism regionalistycznych.

The paper attempts to place the concept of a ‘regionalist magazine’ in a cognitive perspective. The author approaches the issue in four sections. Firstly, he defines the range of meaning of the idea of a ‘regionalist magazine’. Next, he moves on to discuss the ideological foundations of regionalist periodicals, including regionalism and the region, as well as the features, tasks and functions of regionalist periodicals. He concludes by presenting types of regionalist periodicals.
The regionalist magazine – concept, criteria, tasks, roles and types Summary
Keywords: czasopismo regionalistyczne; regionalizm; region; typologia prasy; regionalist magazine; regionalism; region; types of regionalist periodicals